BOOKING SYSTEM BASED ON FIXED MATURITY P.T NORTH JAVA SEA GROUP BY USING MICROSOFT VISUAL BASIC 6.0 - Erdiansyah Wiria Sahputra (Jurnal Manajemen Informatika, 2010)
Scientific research aims to create time-based ordering system due in PT NORTHJAVA SEA GROUP, ranging from data input to the preparation of reports by usingMicrosoft Visual Basic 6.0.Scientific research is that a study by collecting data. The authors obtained data byinterviewing the leaders and employees associated with the company.From this research we can conclude that by using the computerized will get the easeand speed up the ordering process.